Quantity of cholesterol in butter from Zagreb market - Željka Cvrtila; Bela Njari; Davorin Bažulić; Mirza Hadžiosmanović; Branimir Mioković; Lidija Kozačinski; Darinka Pranjić (Mljekarstvo, 2001)
In this article the quantity of cholesterol in butter - a representative of dairy products with known high quantity of milk fat, is determined. The results show that the quantity of milk fats for the butter samples from domestic production (n=17) was 83.9 %, and from the industrial production (n=5) 85.2 %. Average cholesterol quantities, in before mentioned samples, were 227 mg/100g or 22 mg of cholesterol per 100 g of sample. The results show that the increase of milk fats does not strictly influence cholesterol increase in the individual butter sample.